Clinical Response to Two Formulas in Infants with Parent-Reported Signs of Formula Intolerance: A Multi-Country, Double-Blind, Randomized Trial. (September 2020) - Vivatvakin, Boosba; Estorninos, Elvira; Lien, Reyin; Lee, Hung Chang; Hon, Kam Lun Ellis; Lebumfacil, Jowena; Cercamondi, Colin I; Volger, Sheri
Background: Signs of feeding intolerance are common in formula-fed infants. We evaluated the clinical response to a partially hydrolyzed 100% whey protein formula with high sn -2 palmitate and reduced lactose (FA) and to an alpha-lactalbumin-enriched whey-predominant intact protein formula with full lactose (FB) in healthy full-term infants with parent-reported signs of feeding intolerance. Methods: In a double-blind, parallel-group trial in 6 Asian study centers, exclusively formula-fed infants aged 30 to 90 days, whose parents reported fussiness-crying for ≥2 hours/day plus gassiness and/or stooling difficulty, and intended to switch formula, were randomly assigned to FA (n = 130) or FB (n = 129) for 14 days. Primary endpoint was daily duration of fussiness-crying. Secondary endpoints included gassiness, spitting-up, vomiting, sleep pattern, Infant Gastrointestinal Symptom Questionnaire (IGSQ) Index, infant temperament and maternal anxiety. Results: Mean ± SE minutes/day of fussiness-crying in the 256 analyzed infants (FA, n = 127 and FB, n = 129) substantially decreased from baseline to study end in FA (291 ± 14 to 140 ± 8; –52%, P  < .001), and FB (313 ± 14 to 153 ± 11, –51%, P  < .001) with no difference between groups. Similarly, gassiness, spitting-up, vomiting and sleep pattern significantly improved by study end for both formulas. Mean ± SE IGSQ index scores significantly decreased from baseline to study end (FA: 44.5 ± 0.9 to 28.6 ± 0.7; FB: 44.5 ± 0.8 to 29.0 ± 0.7; P  < .001) with no differences between groups. Infant temperament and maternal anxiety also improved significantly in both groups by study end. Conclusion: Switching from standard, full-lactose, intact whey/casein infant formulas to either study formula resulted in an improvement of gastrointestinal symptoms and associated behaviors in infants with signs of feeding intolerance. Trial Registration: https://clinicaltrials.gov, NCT02021058